THE PHYSICAL COMPETENCE OF FUTURE TEACHERS AS AN INPUT TOWARDS THE QUALITY OF THE PEDAGOGICAL ACTIVITY CONCEPT - Vecenane, Helena; Bethere, Dina; Usca, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The indicators of physical competence in scientific research studies and normative documents of education systems are defined differently. However, the consolidation of research evidence confirms that in this area the knowledge and skills of the person imply taking responsibility for health and well-being of one’s body, motoric skills, and ability to regulate and physically adapt to the surrounding environment. Undoubtedly, the family plays a major role in the development of children's physical competence. At the same time in this context the input of educational programmes is significant together with the individual physical competence of a teacher and his/her understanding about how to ensure its quality in one’s own work and in the concept of educational system.The aim of the research reflected in this publication is to analyse the physical competence of the students of Teacher Programmes as a resource for the development of the concept of their further pedagogical work. For this purpose, the emerging teachers have been surveyed using the methodology developed by Corbin et al. (2008). For statistical analysis of the research data the SPSS 22.0 programme was employed: a method of descriptive statistics, Kruskal-Wallis test, and Kendall's tau-b correlation test.